PENGARUH SENAM TAI CHI TERHADAP PENINGKATAN KESEIMBANGAN DINAMIS PADA LANJUT USIA - Swandari, Atik; Purwanto, Bambang; Sulistiawati, Sulistiawati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: to prove the effect of Tai chi on the increase of dynamic balance in the elderly.Â Methods: One group pretest posttest design with 23 subjects of elderly people aged 60-75 years old and given Tai chi twice a week for 30 minutes within one month (8 times). Measurement: Functional Reach Test (FRT) and Time Up and Go Test (TUG). Analysis: Normality test by Saphiro Wilk as well as pretest-posttest different test with paired T-test. Â Results: Based on the analysis of normality test by Saphiro Wilk on the pretest and posttest, the obtained result is p>0.05 which means the data is normally distributed. In the meantime, the analysis of pretest-posttest difference test with paired T-test results in dynamic balance value before and after Tai chi as much as p<0.05 (p=0.000); and, it also generates the dynamic balance value before and after Tai chi with TUG as much as p<0.05 (p=0.000). This means there is a significant difference between before and after the treatment when measured by Functional Reach Test (FRT) and Time Up and Go Test (TUG). Â Conclusion: Tai chi improves the dynamic balance in the elderly.